The Role of Absorptive Capacity for Business Intelligence and Analytics for Value Creation: In Viet Nam Business - Loc, Luu Duc (Digital Repository of Theses - SSBM Geneva, 2025)
In today's data-centric business world, Business Intelligence (BI) and Analytics play a crucial role in decision-making and performance improvement. However, the success of these initiatives relies on an organization's absorptive capacity—the ability to acquire, assimilate, and apply external knowledge effectively. This study investigates the significance of absorptive capacity for BI and Analytics in creating value for organizations. Through a mixed-method research design, quantitative surveys and qualitative interviews were conducted. The findings demonstrated a strong positive correlation between absorptive capacity and the adoption of BI and Analytics technologies. Organizations with higher absorptive capacity were more successful in leveraging data for decision-making and value creation. The qualitative analysis revealed that a culture of organizational learning, knowledge sharing, and openness to external knowledge sources were key factors promoting absorptive capacity development. Enhancing absorptive capacity empowers organizations to harness the full potential of data-driven insights, leading to improved decision-making and performance. By fostering a culture of continuous learning, organizations can optimize their BI and Analytics initiatives, gain a competitive edge, and achieve sustainable growth in the dynamic business landscape. In conclusion, absorptive capacity plays a pivotal role in maximizing the value derived from BI and Analytics. Organizations should prioritize developing their absorptive capacity to capitalize on data-driven opportunities, thereby enhancing overall success and driving business growth.